Alfonso Camín in Mexico and his editorial work in the magazines Rojo y Gualda and Castillos y Leones, 1916-1921 - Gil Lázaro, Alicia (Revista Complutense de Historia de América, 2022)
This article deals with the work that the Asturian writer and journalist Alfonso Camín developed during his first sojourn in Mexico, between 1917 and 1921. Specifically, the text analyses his activity as an editor of the magazines Rojo y Gualda and Castillos y Leones in the Mexican capital. The journalistic activity of the Spanish community in Mexico had slowed down as a result of the armed phase of the Mexican revolution and almost all the Spanish daily newspapers ceased to be published. However, this was not the end of the Spanish press in Mexico, for since 1915 -and for the next two decades- the daily newspapers were replaced by weekly and monthly illustrated magazines that focused on cultural affairs, rather than on political questions. These magazines were the meeting point around which a dynamic group of immigrant Spanish journalists who had arrived to Mexico during the last years of the Porfiriato was formed. Many of these journalists were linked to intellectual and journalistic networks of Mexico, Spain and Latin American countries, especially Cuba. Camín and the rest of the editors of those magazines shared common ideas about Hispano-Americanism and used their publications as channels of dissemination of that current of thought in Mexico, especially among the Spanish community, which built its identity discourse out of it. In some respects, Rojo y Gualda and Castillos y Leones were a heirs to the Spanish journalism that had been made in Mexico during the Porfiriato, but at the same time they full participated in the Transatlantic intellectual exchanges of the time.